Gambaran Sanitasi Peralatan Pengolahan Gethuk Pisang ”X” di Desa Kepung Kabupaten Kediri - Ananda Putri E. N.; Tutut Pujianto (Poltekkes Kemenkes Yogyakarta, 2021)
High quality gethuk pisang should implement sanitation principles, such as for the processing equipments. The research purpose was to know the implementation of processing equipment sanitation at home industry X in Kediri, i.e. at the steps of banana steaming, ingredients mixing and gehuk pisang pressing. It was a descriptive study, and the data collection instrumen was using a checklist for equipment sanitation. The study results show that the equipment which have contact with food doesn’t meet equipment sanitation requirements i.e. <100%, while those which do not have contact, meet the requirements or 100%. The food contacted equipments must be made from safe and harmless materials for health. The next studies are recommended to evaluation the other aspects of sanitation, such as food sanitation, water sanitation, environ- mental sanitation etc.